Cumplimiento de la Ordenanza 0041 para prevenir y erradicar la violencia de género en el cantón Loja, año 2022 - Vera Vega, Nadia Maitee (2023)
The present Work of Curricular Integration aims to diagnose compliance with Ordinance 0041 to prevent and eradicate gender violence in the Loja canton, year 2022, therefore, it proceeded to identify the mechanisms implemented by the Decentralized Autonomous Government of Loja for its application; determine the changes generated as a result of its implementation and with the recognition of gaps presented in its execution, an improvement plan was designed for its effective application. The research was developed with a qualitative approach from a non-experimental design and was established as an exploratory type, descriptive and action-research, and the inductive and analytical-synthetic methods were used. For the fulfillment of objectives, two techniques were applied, among them we have first the semi-structured interview with open questions, applied to the delegates of the institutions responsible for ensuring the rights of individuals and applying ordinance 0041; the observation sheet that made it possible to verify the compliance of the actions contained in the Cantonal Plan by the Cantonal System; and techniques such as the analysis of internal and external DAFO factors that diagnosed the current situation of the implementation of the ordinance, and finally, the Ishikawa diagram to know the causes that generate the weaknesses found in the DAFO analysis. Resulting in the application of two mechanisms used by the Gad de Loja to ensure compliance with the ordinance, likewise, the different positive changes generated by its application in the canton were evidenced, and finally, based on the deficiencies found, it was considered necessary to develop strategies and activities contained in an improvement plan to guarantee their compliance.